The physical origin of supercompetitive accretion during the formation of the first supermassive black holes - Schleicher, Dominik R. G.; Reinoso, Bastián; Klessen, Ralf S. (Monthly notices of the Royal Astronomical Society, 2023)
Numerical simulations have shown the occurrence of a scenario termed 'supercompetitive accretion', a term that describes a situation where only the central few objects grow supermassive while a larger number of stars compete for the reservoir, with significant accretion flows of greater than or similar to 0.1 M-circle dot yr(-1). This scenario particularly implies that the presence of fragmentation will not necessarily impeed the formation of a central massive object. We, here, explore this phenomenon using analytical estimates for growth via collisions and accretion, considering accretion due to self-gravity as well as Bondi-Hoyle accretion. Particularly, we explore under what conditions the accretion on to the central massive object breaks down, and derive a criterion that depends on the mass of the most massive object and the mass in fragments. For compact clusters with sizes about 0.1 pc, we further find that the mass growth by collisions is comparable to the growth via accretion. Our results are validated through the comparison with numerical simulations, and we overall conclude that supercompetitive accretion is a valid mechanism for the formation of very massive objects in the early Universe.